2006
DOI: 10.2298/aoo0602026s
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide in the therapy of recurrent medulloblastomas

Abstract: BACKGROUND:Recurrence of medulloblastoma appears after 30% to 40% of the surgeries. Different from primary medulloblastoma, in which five-year survival rate is 50%, the survival time of relapses much shorter and only 20% of the patients manage to survive a year. There is a logical need for additional methods of treatment of recurrent medulloblastomas. The aim of the study is to determine the effects of intracavitary and long-term subcutaneous application of Sandostatin (octreotide) on the recurrent medulloblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The clinical utility of somatostatin analogs in the treatment of medulloblastoma was first reported in 2005 in a Serbian series, which presented 10 of 14 children (72%) with a high-risk of relapsing medulloblastoma having disease involution with the use of octreotide alone [ 9 ]. In adults, the previous clinical experience is reduced to a single case reported in 2008 by Glas, et al with a 43-year old man with a relapsing medulloblastoma who achieved sustained disease response with octreotide; unfortunately, he presented with thrombotic thrombocytopenic purpura by the tenth month of administration and, therefore, the treatment was ended [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical utility of somatostatin analogs in the treatment of medulloblastoma was first reported in 2005 in a Serbian series, which presented 10 of 14 children (72%) with a high-risk of relapsing medulloblastoma having disease involution with the use of octreotide alone [ 9 ]. In adults, the previous clinical experience is reduced to a single case reported in 2008 by Glas, et al with a 43-year old man with a relapsing medulloblastoma who achieved sustained disease response with octreotide; unfortunately, he presented with thrombotic thrombocytopenic purpura by the tenth month of administration and, therefore, the treatment was ended [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Case reports in the literature show encouraging results with second line chemotherapy [10,11], anti-angiogenic drugs [12] and targeted therapy for example with somatostatin analogues [13,14]. Th ese therapies may further improve prognosis and enable "living with cancer" for years even for patients with fatal prognosis like disseminated spinal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite lacking suitable chemotherapy, a therapeutic approach in combination has been employed in brain tumor treatment. Stefanović et al, for the first time, described the use of SST and its analogs in the treatment of medulloblastoma in children [ 171 ]. Previous studies have shown encouraging results in the treatment of medulloblastoma following intrathecal administration of radiolabeled SST analogs despite controversial observations with non-radiolabeled OCT [ 143 , 146 ].…”
Section: Role Of Somatostatin and Somatostatin Receptors In Brain Cancermentioning
confidence: 99%